Adaptive consensus algorithms for real‐time operation of multi‐agent systems affected by switching network events. (20th October 2016) - Muñoz, Filiberto; Espinoza Quesada, Eduardo Steed; La, Hung M.; Salazar, Sergio; Commuri, Sesh; Garcia Carrillo, Luis Rodolfo
Summary: We propose a control strategy based on distributed adaptive leader‐follower consensus algorithms for multi‐agent systems (MAS) affected by switching network events. The strategy allows each agent in the MAS to compute its own control input based on local information and information coming from its neighbors. In this sense, MAS distributed control laws are obtained where the coupling gain of the associated communication graph is adapted dynamically in real‐time. The consensus algorithm is extended with a switching network topology approach, which ensures appropriate performance even when the MAS network topology is prone to arbitrary switching. A real‐time experimental application is presented, where a MAS consisting of four rotorcraft UAS successfully performed the tasks of autonomously approaching and escorting a leader, even in the situation when the network topology was arbitrarily changing. Additionally, a Lyapunov stability analysis is included, which demonstrates that the tracking errors between leader and follower agents converge asymptotically to zero. Copyright © 2016 John Wiley & Sons, Ltd.